Effects of bleaching with carbamide peroxide gels on microhardness of restoration materials - Campos, Inger; Briso, André Luiz Fraga [UNESP]; Pimenta, Luiz André Freire; Ambrosano, Gláucia (Wiley, 2003)
The objective of this in vitro study was to quantitatively assess the effects of bleaching with 10 and 15% carbamide peroxide (CP) on restoration materials by performing superficial microhardness analysis. Acrylic cylindrical containers (4 x 2 mm) were filled with the following restoration products: Charisma (Heraues Kulzer, Vila Santa Catarina, São Paulo, Brazil), Durafill VS (Heraeus Kulzer), Vitremer (3M, Sumaré, São Paulo, Brazil), Dyract (Dentsply, Petrópolis, Rio de Janeiro, Brazil), and Permite C (SDI, São Pauio, São Paulo, Brazil). Sixty samples were prepared of each restoration material. Twenty samples received bleaching treatment with 10% CP, 20 samples received bleaching treatment with 15% CP, and 20 samples were kept submerged in artificial saliva, which was replaced daily. The treatment consisted of immersion of the specimens in 1 cm3 of CP at 10 and 15% for 6 hours per day during 3 weeks, whereupon the test specimens were washed, dried, and kept immersed in artificial saliva for 18 hours. Then the test and control specimens were analyzed using a microhardness gauge. The Knoop Hardness Number (KHN) was taken for each test and control specimen at five different locations by applying a 25 g force for 20 seconds. The values obtained were transformed into KHNs and the mean was calculated. The data were submitted to statistical analysis by analysis of variance and Tukey test, p < .05. The means/standard deviations were as follows: Charisma: CP 10% 38.52/4.08, CP 15% 34.31/6.13, saliva 37.36/4.48; Durafill VS: CP 10% 18.65/1.65, CP 15% 19.38/2.23, saliva 18.27/1.43; Dyract AP: CP 10% 30.26/2.81, CP 15% 28.64/5.44, saliva 33.88/3.46; Vitremer: CP 10% 28.15/3.04, CP 15% 17.40/3.11, saliva 40.93/4.18; and Permite C: CP 10% 183.50/27.09, CP 15% 159.45/5.78, saliva 215.80/26.15. A decrease in microhardness was observed for the materials Dyract AP, Vitremer, and Permite C after treatment with CP at 10 and 15%, whereas no effect on either of the two composites (Charisma and Durafill) was verified. CLINICAL SIGNIFICANCE: The application of the carbamide peroxide gels at 10 and 15% did not alter the microhardness of the composite resins Charisma and Durafill. In situ and clinical studies are necessary to enable one to conclude that the reduction in microhardness of the materials effectively results in clinical harm to the restorations.
Keywords: peroxide; saliva substitute; unclassified drug; urea peroxide; controlled study; dental care; drug effect; gel; hardness; human; human tissue; Analysis of Variance; Compomers; Composite Resins; Dental Amalgam; Dental Materials; Dental Restoration, Permanent; Dental Stress Analysis; Drug Combinations; Glass Ionomer Cements; Hardness; Materials Testing; Oxidants; Peroxides; Time Factors; Tooth Bleaching; Urea